(untitled) (International Journal of Food and Nutritional Sciences, 2023)
We have the like the glass cliff (which restricts women from dangerous leadership parts), and the glass ceiling (which keeps women blocked since upward movement in their careers), both manifestations of this insidious gender inequality that remains present within the workplace. The present study finds its motivation in this backdrop and aims to conduct an empirical investigation of the aforementioned barriers for working women of Nagpur District and their attitude-related outcomes such as job satisfaction, career aspirations, psychological well-being and organizational commitment. In Nagpur, data was collected from a structured survey of female professionals working in various industries, using a quantitative study method. This study employs statistical techniques including regression modeling and correlation analysis to inspect the association amongst respondents’ glass ceiling and glass cliff experiences and behavioral and attitudinal outcomes. The research finds that job satisfaction and job career motivation ante at the glass ceiling are adversely affected resulting in high turnovers. Exposure to the glass cliff creates workplace anxiety and stress yet, sometimes, it does also lead to resilience for women in leadership. This exploration highlights the necessity for policies that are gender-inclusive, mentorship programs tailored to support female professionals, and initiatives aimed at fostering women within leadership roles, all of which would serve to mitigate the highlighted effects and ensure equitable career progression across genders. The findings contribute to the wider debate on workplace gender dynamics to help inform policymakers, corporate leaders and HR professionals to ensure more sustainable career pathways for women.